Disorganisation: a possible cause of apparent conjoint twinning. Issue 10 (October 1991) - Petzel, M A; Erickson, R P
Abstract : A patient with duplications of the internal organs and external structures of the lower half of the body might have traditionally been explained by incomplete twinning. The presence of a fifth digit-like structure protruding from the lower abdomen and facial and cranial abnormalities suggested that, instead, he might be an example of the disorganisation mutant. However, the presence of cardiac defects was not readily explained by invoking the presence of this mutation.